2017
DOI: 10.1038/ng.3815
|View full text |Cite
|
Sign up to set email alerts
|

Germline mutations in ABL1 cause an autosomal dominant syndrome characterized by congenital heart defects and skeletal malformations

Abstract: ABL1 is a proto-oncogene well known as part of the fusion gene BCR-ABL in the Philadelphia chromosome of leukemia cancer cells1. Inherited germline ABL1 changes have not been associated with genetic disorders. Here we report ABL1 germline variants co-segregating with an autosomal dominant disorder characterized by congenital heart disease, skeletal abnormalities, and failure to thrive. The variant c.734A>G (p.Tyr245Cys) was found as de novo or co-segregating with disease in five individuals (families 1-3). Add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 24 publications
4
46
0
Order By: Relevance
“…However, pathway analysis for the highest 5% and lowest 5% genes expressed in RNAseq data from dermal fibroblasts obtained in one subject (Female 13) showed enrichment in cell cycle control of chromosomal replication and double‐strand break repair pathways (Table S2). Future studies will elucidate whether individuals carrying DDX3X variants are at risk for the development of malignancies 21. In summary, we identified 31 unrelated patients with causal variants in DDX3X and expanded the genotypic and phenotypic spectrum of DDX3X ‐related disorders.…”
Section: Discussionmentioning
confidence: 94%
“…However, pathway analysis for the highest 5% and lowest 5% genes expressed in RNAseq data from dermal fibroblasts obtained in one subject (Female 13) showed enrichment in cell cycle control of chromosomal replication and double‐strand break repair pathways (Table S2). Future studies will elucidate whether individuals carrying DDX3X variants are at risk for the development of malignancies 21. In summary, we identified 31 unrelated patients with causal variants in DDX3X and expanded the genotypic and phenotypic spectrum of DDX3X ‐related disorders.…”
Section: Discussionmentioning
confidence: 94%
“…This study reports six patients carrying de novo heterozygous missense variants with phenotypes overlapping with the original study (Wang et al, 2017). ABL1 has two isoforms, 1a (NM_005157.5) and 1b (NM_007313.2), as a result of an alternatively spliced first exon.…”
Section: Patientmentioning
confidence: 75%
“…He had global developmental delay, failure to thrive, hypotonia, and severe feeding difficulties requiring gastrostomy tube for insertion, tetralogy of Fallot, and microcephaly (50.5 cm; <3rd centile at 9 years of age based on Norwegian growth charts (Juliusson et al, 2009(Juliusson et al, , 2013 Complementary DNA (cDNA) constructs, cell culture, and immunoblotting in the functional studies were performed as previously described (Wang et al, 2017). The antiphospho-ABL1 antibody (#5300, Cell Signaling Technology, Danvers, MA) used in the original study (Wang et al, 2017) All reported heterozygous missense variants identified by exome sequencing in this study were found to be de novo ( Figure S1; Tables S1 and S2). We identified the variant c. 407C>T (p.Thr136Met) (Figure 1).…”
Section: Patientmentioning
confidence: 99%
“…Variants reported in this study were deposited to ClinVar (https://www.ncbi.nlm.nih.gov/clinvar/). Clinical trio exome sequencing for Families 1 and 3 at Baylor was performed as previously described (Wang et al, ; Yang et al, ). Briefly, genomic DNA samples were fragmented, ligated to Illumina multiplexing paired‐end adaptors, amplified with indexes added, and hybridized to exome capture reagent (Roche NimbleGen).…”
Section: Methodsmentioning
confidence: 99%
“…Variants reported in this study were deposited to ClinVar (https:// www.ncbi.nlm.nih.gov/clinvar/). Clinical trio exome sequencing for Families 1 and 3 at Baylor was performed as previously described (Wang et al, 2017;Yang et al, 2013) (Yang et al, 2013). Reads were aligned to human genome build GRCh37/UCSC hg19 and analyzed for sequence variants using a custom-developed analysis tool.…”
Section: Clinical Exome Sequencing and Data Analysismentioning
confidence: 99%